2018
DOI: 10.1111/bcpt.13137
|View full text |Cite
|
Sign up to set email alerts
|

Expression of clinically relevant drug‐metabolizing enzymes along the human intestine and their correlation to drug transporters and nuclear receptors: An intra‐subject analysis

Abstract: The oral bioavailability of many drugs is highly influenced not only by hepatic but also by intestinal biotransformation. To estimate the impact of intestinal phase I and II metabolism on oral drug absorption, knowledge on the expression levels of the respective enzymes is an essential prerequisite. In addition, the potential interplay of metabolism and transport contributes to drug disposition. Both mechanisms may be subjected to coordinative regulation by nuclear receptors, leading to unwanted drug‐drug inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 68 publications
8
43
1
Order By: Relevance
“…Intercorrelations were found between P450, between UGTs, between P450 and UGTs, and between DMEs and transporters, in line with that previously established in studies using mRNA expression levels at the mRNA level; strong intercorrelations have been reported between CYP3A4-ABCB1 (P-gp) and UGT1A1-ABCC2 (MRP2) (Drozdzik et al, 2014;Bruckmueller et al, 2017;Fritz et al, 2019). In the present study, similar strong intercorrelation was observed at the protein level between these protein pairs.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Intercorrelations were found between P450, between UGTs, between P450 and UGTs, and between DMEs and transporters, in line with that previously established in studies using mRNA expression levels at the mRNA level; strong intercorrelations have been reported between CYP3A4-ABCB1 (P-gp) and UGT1A1-ABCC2 (MRP2) (Drozdzik et al, 2014;Bruckmueller et al, 2017;Fritz et al, 2019). In the present study, similar strong intercorrelation was observed at the protein level between these protein pairs.…”
supporting
confidence: 92%
“…Challenges associated with obtaining intestinal tissue samples increase the value of studies reporting the actual protein abundances as opposed to mRNA levels. There are a number of reports on mRNA expression data of genes encoding DMEs and drug transporters in the human small intestine (Thörn et al, 2005;Clermont et al, 2019;Fritz et al, 2019). However, caution should be exercised in using these values because the relationship between mRNA and protein abundance appears inconsistent (Berggren et al, 2007;Hayeshi et al, 2008), suggesting that mRNA data in a high-turnover tissue such as intestine may have limited utility for PBPK modeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of our study allowed us to investigate interindividual differences and regional distribution of cytochrome P450 isoforms. Our work complements and supports results from previous studies as it reports data on several subjects, as well as multiple sections from the same donors …”
Section: Discussionsupporting
confidence: 90%
“…and Fritz et al . reported similar data in their study measuring protein expression, with a ranking of CYP3A4 > CYP2C9 > CYP2C19 . Since they did not quantify CYP2J2, it is not possible to compare the protein expression of that isoform with our mRNA data …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation